Enabling synergy in IoT: Platform to service and beyond. (1st March 2017) - Andersen, Michael P.; Fierro, Gabe; Culler, David E.
Abstract: To enable a prosperous Internet of Things (IoT), devices and services must be extensible and adapt to changes in the environment or user interaction patterns. These requirements manifest as a set of design principles for each of the layers in an IoT ecosystem, from hardware to cloud services. This paper gives concrete guidelines learned from implementing and deploying a full-stack synergistic IoT platform. We address hardware design concerns and present a reference platform, Firestorm. Upon this platform, we demonstrate firmware and personal-area networking concerns and solutions. Moving out towards larger scales we address local service discovery and syndication, and show how these principles carry through to global operation where security concerns dominate.